KOPACE (KOPI KELOR ACEH) TRANSFORMASI USAHA GEURUBAK KUPI MELALUI INOVASI KOPI KELOR - Asnidar, Asnidar; Fajriah, Agustina Nurul; Dwitya, Yonadiah; Murni, Mayang; Nafaida, Rizky; Nabila, Rozana; Khaira, Cut Ulviatul (Universitas Padjadjaran, 2026)
This Community Service (PKM) program was implemented to address the stagnation of the Geurubak Kupi micro-business in Langsa City, caused by products lacking distinctive characteristics, unsystematic financial management, and conventional marketing strategies. This partnership program involved a series of stages, including outreach, training, technology implementation, mentoring, and evaluation. The main innovation was the development of Acehnese Moringa Coffee (KOPACE), a specialty beverage that combines the flavor of Acehnese coffee with the health benefits of moringa leaves. The implementation of technologies such as a dehydrating oven, a coffee grinder, and a flour grinder ensured product quality and hygiene. Furthermore, financial management training based on simple bookkeeping and production cost calculations helped partners manage their businesses more efficiently. Marketing aspects were also strengthened through training in branding, packaging design, and digital promotion strategies. Evaluation results showed a significant increase in the partners' understanding, with an average improvement of more than 10%–15% in knowledge of moringa coffee processing, financial management, and marketing strategies. KOPACE products are now a new signature product of the Geurubak Kupi business, adding economic value, increasing competitiveness, and opening up broader market opportunities. Thus, this PKM program contributes to the achievement of the Sustainable Development Goals (SDGs), specifically Decent Work and Economic Growth, Responsible Consumption and Production, and Good Health and Well-being.Kegiatan Pengabdian kepada Masyarakat (PKM) ini dilaksanakan untuk menjawab permasalahan stagnasi usaha mikro Geurubak Kupi di Kota Langsa yang disebabkan oleh produk tanpa ciri khas, manajemen keuangan yang tidak tersistematis, serta strategi pemasaran yang masih konvensional. Melalui program kemitraan ini, dilakukan serangkaian tahapan meliputi sosialisasi, pelatihan, penerapan teknologi, pendampingan, dan evaluasi. Inovasi utama kegiatan adalah pengembangan produk Kopi Kelor Aceh (KOPACE) sebagai minuman khas yang menggabungkan cita rasa kopi Aceh dengan manfaat kesehatan dari daun kelor. Penerapan teknologi seperti oven dehydrated, mesin grinder kopi, dan mesin grinder tepung memastikan kualitas dan higienitas produk. Selain itu, pelatihan manajemen keuangan berbasis pencatatan sederhana dan perhitungan harga pokok produksi membantu mitra lebih efisien dalam mengelola usaha. Aspek pemasaran juga diperkuat melalui pelatihan branding, desain kemasan, serta strategi promosi digital. Hasil evaluasi menunjukkan adanya peningkatan signifikan dalam pemahaman mitra, dengan rata-rata peningkatan lebih dari 10% pada pengetahuan pengolahan kopi kelor, manajemen keuangan, dan strategi pemasaran. Produk KOPACE kini hadir sebagai ciri khas baru usaha Geurubak Kupi sekaligus memberi nilai tambah ekonomi, meningkatkan daya saing, dan membuka peluang pasar lebih luas. Dengan demikian, program PKM ini berkontribusi pada pencapaian SDGs, khususnya tujuan pekerjaan layak dan pertumbuhan ekonomi, konsumsi-produksi yang bertanggung jawab, serta peningkatan kesehatan dan kesejahteraan masyarakat.